Neutrophil to lymphocyte ratio and red blood cell distribution width as predictors of microalbuminuria in type 2 diabetes mellitus - Vekariya, Sagar; Bahulikar, Arun; Phalgune, Deepak; Beke, Nandkumar (International Journal of Research in Medical Sciences, 2025)
Background: Diabetic nephropathy (DN) is a common and feared complication of diabetes mellitus, linked to higher morbidity and mortality rates. Very few studies have assessed the possible clinical value of biomarkers such as neutrophil-to-lymphocyte ratio (NLR) and red blood cell distribution width (RDW) in DN in type 2 diabetes mellitus (T2DM) patients. The present cross-sectional observational study aimed to find the correlation of NLR and RDW with microalbuminuria in T2DM patients. Methods: One hundred and sixty-nine patients aged ≥40 years of either sex, with duration T2DM >4 years, and diagnosed according to the American Diabetes Association criteria, were included in this cross-sectional observational study. NLR, RDW and urine microalbumin were noted. The primary outcome measures were to find the correlation between NLR and RDW with microalbuminuria, whereas the secondary outcome measures were to study the predictive value of NLR and RDW for microalbuminuria in T2DM patients. Results: There was a significant positive correlation between NLR and microalbuminuria (r=0.165) and a significant negative correlation between RDW and microalbuminuria (r=-0.159). The mean serum albumin and NLR were significantly higher in patients having microalbuminuria. The sensitivity of NLR and RDW to predict microalbuminuria was 82.4% and 64.7% respectively. Conclusions: NLR and RDW significantly correlated with microalbuminuria and have good sensitivity for microalbuminuria in T2DM patients. NLR and RDW are cheap and inexpensive methods for detecting DN.